Biomaterials and Nanotherapeutics for Enhancing Skin Wound Healing - Das, Subhamoy; Baker, Aaron B. (Frontiers in Bioengineering and Biotechnology, 2016)
Wound healing is an intricate process that requires complex coordination between many cells and an appropriate extracellular microenvironment. Chronic wounds often suffer from high protease activity, persistent infection, excess inflammation, and hypoxia. While there has been intense investigation to find new methods to improve cutaneous wound care; the management of chronic wounds, burns, and skin wound infection remain challenging clinical problems. Ideally, advanced wound dressings can provide enhanced healing and bridge the gaps in the healing processes that prevent chronic wounds from healing. These technologies have great potential for improving outcomes in patients with poorly healing wounds but face significant barriers in addressing the heterogeneity and clinical complexity of chronic or severe wounds. Active wound dressings aim to enhance the natural healing process and work to counter many aspects that plague poorly healing wounds including excessive inflammation, ischemia, scarring and wound infection. This review paper discusses recent advances in the development of biomaterials and nanoparticle therapeutics to enhance wound healing. In particular, this review focuses on the novel cutaneous wound treatments that have undergone significant preclinical development or currently used in clinical practice.